Twentieth-Century Latin American Literary Studies and Cultural Autonomy - Naomi Lindstrom (Studies in 20th & 21st Century Literature, 1995)
Since the 1920s, when scholars first began to specialize in Latin American writing, the subject of Latin American literary studies has grown from a small subset of Spanish and Portuguese literary research and teaching to become the largest field within Hispanism and a significant presence in comparative literature. The expansion of their place in the academic world has often prompted students of Latin American literature to wonder whether, in being swept into the mainstream, their field has not left out of account the historical situations of Latin American nations. These reflections lead critics back to a problem that has troubled Latin American thinkers since Independence: the achievement, or erosion, of cultural autonomy. Though undeniably close to major powers, the Latin American nations are unequal partners in trade and cultural exchange. Corresponding to their uneven and shifting relations with Europe and later the United States, their cultural life evolves following a distinctive historical dynamic. This article considers recent efforts by scholars and essayists to characterize the features that distinguish Latin America from more politically and economically advantaged nations. Special attention goes to those scholars who, drawing on anthropological research, examine communicative and expressive practices of indigenous origin, and those who borrow from economic theory to view Latin America as shaped by its history of dependence on more powerful nations and regions.
Keywords: Latin American literary studies; comparative literature; cultural autonomy; trade; cultural exchange; Europe; U.S.; anthropology; anthropological research; economic theory; power; powerful nations